2015
DOI: 10.2169/internalmedicine.54.3714
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fat Thickness in Patients with Prediabetes and Correlation with Other Cardiovascular Risk Markers

Abstract: Objective Prediabetes is a condition between a normal metabolic state and diabetes mellitus, which includes impaired glucose tolerance (IGT), impaired fasting glucose (IFG), or both. Prediabetes is related with undesirable cardiovascular outcomes. Epicardial fat thickness (EFT) has been correlated with cardiovascular risk factors. We herein aimed to assess EFT in prediabetic patients. Methods We evaluated 64 patients with prediabetes and 30 age-and gender-matched healthy subjects. Demographic and anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…VAT contains a large number of inflammatory cells and expresses several hormone receptors, and its adipocytes are metabolically active and sensitive to lipolysis. The increased amount of VAT carries, in general, a great prediction of mortality [11] and EF, which substantially mirrors visceral adiposity rather than general obesity, has been correlated with cardiovascular risk factors [8,13,14]. EFT increases in obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VAT contains a large number of inflammatory cells and expresses several hormone receptors, and its adipocytes are metabolically active and sensitive to lipolysis. The increased amount of VAT carries, in general, a great prediction of mortality [11] and EF, which substantially mirrors visceral adiposity rather than general obesity, has been correlated with cardiovascular risk factors [8,13,14]. EFT increases in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, EF thickness (EFT) is associated with premature coronary artery disease [12] and obstructive sleep apnea [13]. EFT increases in prediabetic patients, regardless of fasting plasma glucose and HbA1c [14], and in patients with type 2 diabetes mellitus and obesity [15], representing a diagnostic criterion for patients with metabolic syndrome [16]. It is also inversely correlated with endothelial function [17].…”
Section: Introductionmentioning
confidence: 99%
“…7,130,141 Diabetes is accompanied by epicardial adipose expansion and inflammation 142 ; when diabetes and obesity coexist, each contributes to the volume of epicardial fat. 143 Epicardial adiposity is strongly associated with insulin resistance 144 and changes in ventricular structure and function. 145 The metabolic syndrome and non-alcoholic fatty liver disease are associated with increases in epicardial fat that are accompanied by proportional degrees of diastolic dysfunction and microvascular injury.…”
Section: Expansion Of Epicardial Adipose Tissue In Patients With Chromentioning
confidence: 99%
“…16,17 In a study by Arpaci et al including 64 prediabetic and 30 healthy subjects, epicardial fat appears to be increased in subjects with prediabetes in comparison to healthy controls. 18 Song et al showed that epicardial fat was increased in subjects with Type 2 diabetes mellitus and obesity. 19 Thus, overall broad evidence is limited so far.…”
Section: Objectivementioning
confidence: 99%